Contraceptive decision-making and women with learning disabilities. (September 2016) - Ledger, Susan; Earle, Sarah; Tilley, Elizabeth; Walmsley, Jan
This article explores contraceptive decision-making for women with learning disabilities. It sets the historical context of reproductive control by highlighting former practices which overtly aimed to prevent women with learning disabilities from conceiving. This is contrasted with a current legislative framework that strongly endorses the human and reproductive rights of women with learning disabilities. The article presents findings from a small-scale, UK-based survey that invited third parties involved in supporting women with learning disabilities with contraceptive decision-making to share their views and experiences. The survey indicated apparent continuities in practice, showing that key decisions over contraceptive care are often made by other people and not by women themselves. The increasing evidence of a gap between policy and practice is explored; this suggests a need for further research, including studies to explore the experiences of women with high support needs where there may be particular issues in relation to the management of menstruation, decision-making and capacity to consent.